Cancer and risk of cerebral venous thrombosis: a case–control study. (1st December 2017) - Silvis, S. M.; Hiltunen, S.; Lindgren, E.; Jood, K.; Zuurbier, S. M.; Middeldorp, S.; Putaala, J.; Cannegieter, S. C.; Tatlisumak, T.; Coutinho, J. M.
Abstract : Essentials The risk of cerebral venous thrombosis (CVT) in patients with cancer is not known. We performed a case‐control study including 594 patients with CVT and 6278 controls. History of cancer increased the risk of CVT approximately 5‐fold. The association was strongest with hematological cancer in the first year after diagnosis. Summary: Background: Cancer is an established risk factor for leg vein thrombosis and pulmonary embolism. Controlled studies assessing the risk of cerebral venous thrombosis (CVT) in patients with cancer have not been performed. Objective: To assess whether cancer is a risk factor for CVT. Patients/Methods: This was a case–control study. We assessed consecutive adult patients with CVT from three academic hospitals from 1987 to 2015, and control subjects from the Dutch MEGA study (Multiple Environmental and Genetic Assessment of risk factors for venous thrombosis). We adjusted for age, sex and oral contraceptive use, and stratified for type of cancer and time since diagnosis of cancer. Results: We included 594 cases and 6278 controls. In total, 53 cases (8.9%) and 160 controls (2.5%) had a history of cancer. Cases were younger (median 42 vs. 48 years), more often female (68% vs. 54%) and more often used oral contraceptives (55% vs. 23%) than controls. The risk of CVT was increased in patients with cancer compared with those without cancer (adjusted odds ratio [aOR], 4.86; 95% confidence interval [CI], 3.46–6.81). Patients with a hematological type of cancer had a higher risk of CVT (aOR, 25.14; 95% CI, 11.64–54.30) than those with a solid type of cancer (aOR, 3.07; 95% CI, 2.03–4.65). The association was strongest in the first year after diagnosis of cancer (hematological aOR, 85.57; 95% CI, 19.70–371.69; solid aOR, 10.50; 95% CI, 5.40–20.42). Conclusions: Our study indicates that cancer is a strong risk factor for CVT, particularly within the first year of diagnosis and in patients with a hematological type of cancer.